Hallowed ebook An unearthly novel. - Hand, Cynthia (Unearthly, 2012)
For months Clara Gardner trained to face the fire from her visions, but she wasn't prepared for the choice she had to make that day. And in the aftermath, she discovered that nothing about being part angel is as straightforward as she thought. Now, torn between her love for Tucker and her complicated feelings about the roles she and Christian seem destined to play in a world that is both dangerous and beautiful, Clara struggles with a shocking revelation: Someone she loves will die in a matter of months. With her future uncertain, the only thing Clara knows for sure is that the fire was just the beginning. In this compelling sequel to Unearthly, Cynthia Hand captures the joy of first love, the anguish of loss, and the confusion of becoming who you are.